Cultivo de crisântemo sob adubação mineral, cinza vegetal e organomineral associado à calagem - Meneghetti, Luana Aparecida Menegaz (2022)
The production of ornamental flowers in Brazil is an activity of great economic importance in the country. For the vigorous development of flowers, it’s necessary to properly manage soil fertility. The objective was to evaluate different types of fertilization under two levels of liming in the development and production of potted chrysanthemum in Oxisol, cultivated in a greenhouse. The experiment was carried out at the Federal University of Rondonópolis, in a greenhouse of the Postgraduate Program in Agricultural Engineering. The experimental design was in randomized blocks, with a 5x2 factorial scheme, with five types of fertilization (incubated wood ash, non-incubated wood ash, organomineral (50% mineral fertilizer and 50% wood ash), mineral fertilizer and control) and two types of liming (with liming and without liming), with five replicates, totaling 50 experimental units (UEs). The soil used in the experiment was the Oxisol and the chrysanthemum cultivar used was the white Singelo. The variables analyzed are plant height, number of leaves, leaf area, root volume, dry mass of roots, chlorophyll index, water use efficiency, total water consumption and soil chemical characteristics (pH, macronutrients and micronutrients). The data were submitted to analysis of variance by the F test, and when significant they were submitted to the Tukey test at 5% probability. The SISVAR software was used to perform the statistical analysis. The productive and phytometric variables were significant only for fertilization in isolation, except for plant height, which was significant for factor liming and fertilization in isolation. There was interaction between the factors in pH. All chemical characteristics and macronutrients were statistically significant for the types of fertilization and liming, except for sulfur, which was significant only for types of fertilization. There was interaction between the factors in the variables aluminum (Al), magnesium (Mg) and base saturation (V%). Regarding micronutrients, except for iron, treatments with liming and fertilizers with wood ash in their composition provided a higher content of these nutrients in the soil. Wood ash reduces the dependence on liming and mineral fertilizer in potted chrysanthemum plants. Organomineral fertilizer is an alternative for reducing the volume of wood ash and the use of mineral fertilizer. Wood ash is an alternative fertilizer for growing potted chrysanthemum.